First New Record and Molecular Identification of Helvella bachu (Ascomycetes) Isolated from Iraq/Mosul - Jehaan Mowafak Al-Rawi; Shimal Younis Abdul-Hadi (International Journal for Research in Applied Sciences and Biotechnology, 2022)
In this study, Helvella mushroom fruiting bodies samples were collected from the Nimrud area, which is located in the south of Mosul - Iraq. These samples were morphologically diagnosed based on the shape and color of the fruiting body and the shape of the ripples, while microscopically diagnosed based on the shape of cysts and ascospores, then they were molecularly diagnosed by DNA sequence data, from F- ITS1 and R- ITS4 nuclear regions. The phylogenetic analyses emphasize that there is a strongly propped lineages conformable to morphological features. As a result of our study we recorded a new rare species of Helvella mushroom in Iraq after China, then we described the distributions and ecology of the new species.